Implementasi Indonesia National Single Window (INSW): Suatu pendekatan Business Intelligence System (BIS) - Muhammad Ibnu Fajar; Arief Rahman (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
This research aims to analyze the factors influencing the implementation of Indonesia National Single Window (INSW) in Directorate of Customs and Excise by Business Intelligence System (BIS) approach. The independent variables used in this study are management commitment and data quality. Meanwhile, the dependent variable includes the implementation of Indonesia National Single Window (INSW) by Business Intelligence System (BIS) approach. This study applies quantitative research method, field research survey method, and closed questionnaires. The sample in this study are 106 employees at the administrative section of executor function in Directorate of Customs and Excise Information at the Head Office of Directorate of Customs and Excise located in Jakarta, Indonesia. Data analysis employed in this study are multiple regression, pearson correlation, and coefficient of determination with SPSS Statistic 17.0. The result shows that management commitment and data quality variables had a significant positive influence toward the implementation of Indonesia National Single Window (INSW) in Directorate of Customs and Excise by Business Intelligence System (BIS) approach.Â Â